Pengaruh Kompensasi Dan Lingkungan Kerja Terhadap Kinerja Pegawai Kantor Sekretariat DPRD Jombang - Septian Ragil Anandita; Niken PujiAstutik; Wisnu Mahendri (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The purpose Of this study was to determine the effect of compensation and work environment on employee performance at Secretariat DPRD Jombang. The method used in this study is a quantitative method. The population in this study amounted to 50 employees and the sample amounted to 50 respondents using a saturated sampling technique. Data was collected by the questionnaire method, which was then analyzed using multiple regression analysis using SPSS version 26. The results showed that partially compensation variable did not exist, influence on employee performance, while the work environment variable influences employee performance. Simultaneously, compensation and work environment variable have a positive effect on employee performance at Secretariat DPRD Jombang. The results of the analysis of the coefficient of determination obtained 0,434 or 43,4% which means that the contribution of compensation and work environment variable to employee performance is 43,4%, while the rest is influenced by other factors outside this regression model.